Organic nitrogen fertilization affecting commercial classification of potatoes cv. Asterix (Research, Society and Development, 2021)
The objective was to verify the influence of different organic fertilizers and nitrogen doses in the commercial classification of potato cultivar Asterix. The experiment was carried out at the Federal University of Fronteira Sul, Horticulture sector. The experimental design was in randomized blocks, with 16 treatments (3 nitrogen sources x 5 doses and 1 control) and 4 repetitions, totaling 64 plots. The variables evaluated were length / transverse diameter - caliber (mm), diameter (mm), fresh weight (g), serious defects (rot, black heart and hollow heart), slight defects (embonized, burnt, rhizoctonioze and vitrification) and defects variables (greening, superficial damage and pinworm perforations). In all the harvested tubers, no greening, burning, rot, rhizochotonioze, black heart and vitrification were observed. There was an increase in the length, diameter and fresh weight of potato tubers of the Asterix cultivar, as the dose of tanned bed used increased. When the fertilizer sources are compared with the control (NPK fertilization), for these variables, the values are higher only for 200 kgN.ha-1   using the tanned bed source. The source of organic fertilizer bed tanned in the dose 200 kgN.ha -1 favored the production of potato tubers cv. Asterix with characteristics suitable for commercial classification, under the conditions imposed by the experiment.